2015
DOI: 10.1097/hp.0000000000000230
|View full text |Cite
|
Sign up to set email alerts
|

Species-Dependent Chelation of 241Am by DTPA Di-Ethyl Ester

Abstract: Diethylenetriaminepentaacetic acid (DTPA) is an FDA approved chelating agent for enhancing the elimination of transuranic elements such as americium from the body. Early access to therapy minimizes deposition of these radionuclides in tissues such as the bone. Due to its poor oral bioavailability, DTPA is administered as an IV injection, delaying access. Therefore a diethyl-ester analog of DTPA, named C2E2, was synthesized as a means to increase oral absorption. As a hexadentate ligand, it was hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…This work uses classical MD simulations, with parameters optimized with density functional theory (DFT) AIMD simulations, to resolve the solution structures of the Gd-DTPA complex in all DTPA protonation states. Although the pK a values of DTPA are known, [8,[28][29][30][31][32] there is unclarity in the literature on the order in which the amines and the carboxylates are protonated. Based on the known protonation states of EDTA and amino acids, [33][34][35][36] and that an NMR study shows that the amine groups of DTPA correspond to the higher pK a values, [36] as well as the expectation of symmetric protonated structures, [36] we assigned protons to be incrementally added to DTPA to the sites in the order shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…This work uses classical MD simulations, with parameters optimized with density functional theory (DFT) AIMD simulations, to resolve the solution structures of the Gd-DTPA complex in all DTPA protonation states. Although the pK a values of DTPA are known, [8,[28][29][30][31][32] there is unclarity in the literature on the order in which the amines and the carboxylates are protonated. Based on the known protonation states of EDTA and amino acids, [33][34][35][36] and that an NMR study shows that the amine groups of DTPA correspond to the higher pK a values, [36] as well as the expectation of symmetric protonated structures, [36] we assigned protons to be incrementally added to DTPA to the sites in the order shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…99 More recently, while focusing on bioavailability enhancement, Jay and coworkers prepared and evaluated a series of Dtpa esters for their physico-chemical properties and permeability characteristics. 95,[100][101][102][103][104] the penta-ethyl and di-ethyl esters of Dtpa, referred to as C2e5 and C2e2 13, respectively, initially emerged as candidates for further development. however, although C2e5 was shown efficacious in a 241 am wound-contamination animal model, 103,104 concerns were raised over its hepatotoxicity and potential to form up to 10 metabolites.…”
Section: Structural Modifications Of Dtpamentioning
confidence: 99%
“…recent studies reported its decorporation efficacy in beagle dogs, using the 241 am nitrate inhalation contamination model (vide supra), and suggested that it is well tolerated at therapeutic levels. 95,101 Finally, a comprehensive assessment of the genotoxic potential (including the in vitro bacterial reverse mutation ames test, mammalian cell chromosome aberration cytogenetic assay and an in vivo micronucleus test), indicated that C2e2 is not mutagenic or clastogenic. Further efficacy and toxicity studies for C2e2 are ongoing at this time, making this compound a promising orally available candidate for transuranic actinide chelation.…”
Section: Structural Modifications Of Dtpamentioning
confidence: 99%
“…In vivo studies in rats report de-esterification of C2E5 mainly into the tri-and di-ethyl esters C2E3 and C2E2 with some DTPA also present (Zhang et al, 2013b). In vitro binding experiments using human, rat, and dog plasma, suggest that C2E2 is an effective chelator of Am (Huckle et al, 2015a), and this hypothesis is supported by efficacy study following oral administration of C2E2 in beagle dogs (Huckle et al, 2015b). Thus, to be effective, when applied transdermally, C2E5 needs to be metabolized to C2E2 in the body.…”
Section: Downloaded Frommentioning
confidence: 99%